DNA supercoiling and the Lrp protein determine the directionality of fim switch DNA inversion in Escherichia coli K-12 - DORMAN, CHARLES; SMITH, STEPHEN (My University, 2006)
Site-specific recombinases of the integrase family usually require cofactors to impart directionality in the recombination reactions that they catalyze. The FimB integrase inverts the Escherichia coli fim switch (fimS) in the on-to-off and off-to-on directions with approximately equal efficiency. Inhibiting DNA gyrase with novobiocin caused inversion to become biased in the off-to-on direction. This directionality was not due to differential DNA topological distortion of fimS in the on and off phases by the activity of its resident P(fimA) promoter. Instead, the leucine-responsive regulatory (Lrp) protein was found to determine switching outcomes. Knocking out the lrp gene or abolishing Lrp binding sites 1 and 2 within fimS completely reversed the response of the switch to DNA relaxation. Inactivation of either Lrp site alone resulted in mild on-to-off bias, showing that they act together to influence the response of the switch to changes in DNA supercoiling. Thus, Lrp is not merely an architectural element organizing the fim invertasome, it collaborates with DNA supercoiling to determine the directionality of the DNA inversion event.
PUBLISHED
Highlighted in 'Microbe' (formerly 'ASM News') published by the American Society for Microbiology
Keywords: Microbiology; Genes & Society; Immunology, Inflammation & Infection